ANALISIS YURIDIS PENYELESAIAN KREDIT MACET OBJEK HAK TANGGUNGAN YANG DIEKSEKUSI MELALUI PENJUALAN DIBAWAH TANGAN DALAM PRAKTEK PERBANKAN ( Studi di PT. Bank Tabungan Negara Lhokseumawe dan PT. Bank Danamon Indonesia Unit Simpan Pinjam Lhokseumawe ) - SUGENG HARTONO (PREMISE LAW JURNAL, 2016)
In a banking credit contract, the Bank as the creditor usually performs tasks for collateral in order to secure the channeling of its credit according to Law on Hypothecation No. 4/1996 which states that the specific characteristics of hypothecation are firm, simple, and positive in the implementation of its execution when debtors breach the contract (default). The result of the research shows that the legal domicile and process of settling nonperforming loan executed through underhanded sale can only be done when it is estimated that the auction process does not yield the highest price according to Article 20 of Law on Hypothecation No. 4/1996 with all its requirements. The implementation of settling nonperforming loan executed through underhanded sale should regard the right and obligation of debtors and creditors so that legal protection can be made and it does not harm any parties in implementing the execution. Keywords: Execution through Underhanded Sale, Nonperforming Loan, Hypothecation